2007
DOI: 10.1063/1.2815629
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ferromagnetic properties in Al-doped Zn1−xCoxO nanowires synthesized by water-assistance reactive vapor deposition

Abstract: The Zn1−xCoxO and Al-doped Zn1−xCoxO nanowires have been synthesized by the water-assistance reactive vapor deposition method. No Co precipitates appeared in the both kinds of ZnO nanowires according to the results observed by high-resolution transmission electron microscope, x-ray diffraction, and electron energy-loss spectroscopy, revealing that the magnetism of the ZnO nanowires was independent of the Co precipitates. The Al-doped Zn1−xCoxO nanowires show much stronger ferromagnetism than Zn1−xCoxO nanowire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…The majority of the works on DMSs of one-dimensional ZnO nanomaterials are mainly focused on Mn or Co ions doped ZnO nanowires and nanobelts [15][16][17][18]. Our group has also done some works on Co + or Co-Al doped ZnO nanowires [19,20]. However, in most of these works, doping is realized during the synthesis of materials.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the works on DMSs of one-dimensional ZnO nanomaterials are mainly focused on Mn or Co ions doped ZnO nanowires and nanobelts [15][16][17][18]. Our group has also done some works on Co + or Co-Al doped ZnO nanowires [19,20]. However, in most of these works, doping is realized during the synthesis of materials.…”
Section: Introductionmentioning
confidence: 99%
“…Without Cu, the Zn-CoO nanowires in Fig. 3(a) show a number of sharp peaks corresponding to the wurtzite ZnO structure, as well as a single weak, broad peak from cubic Co 3 In the low Cu codoped nanowires ( Fig. 3(b)) some of the ZnO peaks have been suppressed, and those that remain are weaker than without Cu codoping.…”
Section: Co and No Cu Ions Figures 1(b) And 1(c) Show The Polarizatimentioning
confidence: 99%
“…The potential to combine magnetism with semiconducting properties in a single material is a major driving factor behind the recent intense interest into doping magnetic elements into well-known semiconductor materials, such as adding transition metal ion Co into wide bandgap semiconductor ZnO [1]. More recently, attention has focused around the prospect of controlling the magnetic properties of such dilute magnetic semiconductors (DMS) through codoping with non-magnetic elements such as Ga [2], Al [3] or Cu [4]. Codoping can optimize the charge carriers for enhanced ferromagnetism [5,6] and has been touted as a way to modify the tendency of the magnetic dopant to cluster into magnetic nano-precipitates [7].…”
mentioning
confidence: 99%
“…Therefore, some work has been contributed with additional dopants to enhance or induce ferromagnetism in ZnO:Co systems. In the case of (Co, Al)-codoped ZnO, for example, Liao et al [8] used the water-assistance reactive vapor deposition method and Liu et al [9] used a simple solgel technique, although completely different methods have been used, all findings indicated that introducing the additional Al dopant played an important role in enhancing the FM of Co-doped ZnO owing to the increase of the free electron carrier density, while Alaria et al [10] using the co-precipitation method, confirmed that Al ions increase the free carriers concentration, however, those n-type free carriers are not sufficient to create ferromagnetic interactions. Therefore, the reported findings are controversial and more effort should be made to determine the origin of the RT FM in Co and Al co-doped ZnO.…”
Section: Introductionmentioning
confidence: 99%